Siloxane compositions and their use
Patent Information
- Application Number
- CN202180092984.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-02-09
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-02-09
AI Technical Summary
但此硅凝胶的针入度仍较高(针入度值135),在负压环境下使用时会出现气泡或裂痕
[0071]采用本公开的硅氧烷组合物填充大尺寸显示屏与玻璃盖板之间的间隙并排出间隙中的空气,可以使显示屏达到防反光的效果。并且,本公开的硅氧烷组合物固化产物为低针入度的凝胶,且黏性、透光性、耐负压性能优异,可适用于高海拔地区的显示屏的灌封。
Smart Images

Figure CN116888191B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a siloxane composition and its application. Background Technology
[0002] The silicone gel composition is an addition-curing organosiloxane composition, typically containing i) a base polymer, an organopolysiloxane having at least two alkenyl groups such as vinyl groups bonded to silicon atoms, ii) a crosslinking agent, an organohydrogen polysiloxane having at least three hydrogen atoms (i.e., SiH groups) bonded to silicon atoms, and iii) a platinum-based catalyst, which generates a gel through an addition reaction between the SiH groups and the alkenyl groups.
[0003] Traditional silicone gel compositions typically produce cured products with high penetration (i.e., very softness). This means that when used under negative pressure environments, such as at high altitudes, these silicone gels inevitably develop bubbles or peeling due to low gel strength, which is highly undesirable. Increasing the hardness of the cured gel can effectively alleviate these problems; however, higher hardness usually leads to a decrease in the elongation at break and tackiness of the cured gel, affecting its application in display encapsulation or optical bonding.
[0004] Silicone gel compositions using vinyl MQ silicone resin as a crosslinking agent have also been reported in some literature. Example 4 of EP1737504B discloses a silicone gel composition containing 100 parts by weight of vinyl-terminated polydimethylsiloxane with a viscosity of 400 mPa·s, 44 parts by weight of vinyl MQ silicone resin, 18 parts by weight of hydrogen-terminated polydimethylsiloxane with a viscosity of 15 mPa·s, and 0.01% of platinum-based catalyst. However, the penetration of this silicone gel is still relatively high (penetration value 135), and bubbles or cracks may appear when used under negative pressure. Summary of the Invention
[0005] To address the problems existing in the prior art, this disclosure provides a siloxane composition, the silicone gel obtained by curing the composition achieving at least one or more of the following objectives while obtaining a suitable low penetration:
[0006] 1) Higher elongation at break and better resistance to deformation and tensile strength at the same penetration;
[0007] 2) Superior gel viscosity;
[0008] 3) Excellent high temperature resistance. No bubbles or cracks appeared in the gel after aging at 95℃ for 200h. There are two reasons for bubbles or cracks. First, some invisible bubbles expand rapidly at high temperature. If the colloid strength is not enough, the gas will expand and cracks will appear. Second, the substrate warps under high temperature. If the colloid strength is low, it will be pulled apart and cracks will appear.
[0009] 4) Excellent resistance to negative pressure. The gel did not show any bubbles or cracks even after being placed under negative pressure for 3 days. There are two reasons for bubbles or cracks. First, some invisible bubbles expand rapidly under negative pressure. If the colloid strength is not sufficient, the gas will expand and cracks will appear. Second, the substrate warps under negative pressure. If the colloid strength is low, it will be pulled apart and cracks will appear.
[0010] In this disclosure, the term "silicone gel" refers to a cured product containing an organosiloxane as the main component and having a low crosslinking density, having a penetration value from 20 to 200 according to ASTM D1403 (1 / 4 cone). This is consistent with products whose rubber hardness test according to GB / T531-1999 returns a value of zero (rubber hardness value), indicating that the hardness of the product is so low that it shows no valid rubber hardness value.
[0011] The term "penetration" refers to the depth to which a standard needle penetrates perpendicularly into a gel sample under a given load and time. A higher penetration value indicates a softer gel with lower mechanical strength. Since the mechanical strength of a silicone gel increases with increasing crosslinking density, the penetration value decreases; conversely, when the crosslinking density decreases, the mechanical strength decreases, and the penetration value increases. Therefore, the penetration value of a silicone gel can also be used to characterize its crosslinking density. A larger penetration value indicates a lower crosslinking density, and a smaller penetration value indicates a higher crosslinking density.
[0012] In this disclosure, the term "silicone rubber" refers to a cured product containing an organopolysiloxane as a main component, whose measured value (rubber hardness value) in accordance with GB / T531-1999 exceeds zero and displays a valid rubber hardness value.
[0013] In this disclosure, the term "stickiness" refers to a material's property of being slightly sticky to the touch but not exhibiting any significant adhesion to other materials, as opposed to "adhesion." "Adhesion" is a property used to measure the strength of a material's bond with other materials, such as a substrate. This bond is typically achieved through chemical action and is irreversible, meaning that once the material is peeled from its bonded portion, it loses its adhesiveness. In contrast, a material exhibiting "stickiness" typically bonds with other materials through physical action and is reversible, meaning that it retains good adhesion even after being peeled from its bonded portion.
[0014] In this disclosure, unless otherwise specified, "viscosity" is measured using conventional methods in the art.
[0015] The first aspect of this disclosure provides a siloxane composition comprising:
[0016] (a) At least one polyorganosiloxane containing two alkenyl groups bonded to the silicon atoms at the ends of the molecular chain per molecule.
[0017] (b) at least one polyorganosiloxane containing at least three alkenyl groups bonded to silicon atoms per molecule.
[0018] (c) at least one polyorganosiloxane containing two hydrogen atoms bonded to the silicon atoms at the ends of the molecular chain per molecule, and
[0019] (d) at least one hydrogenation silylation catalyst;
[0020] The condition is that the content of component (c) is greater than or equal to 30 wt% of the total weight of the composition, preferably greater than or equal to 40 wt% of the total weight of the composition, and the content of at least one polyorganosiloxane containing at least 3 hydrogen atoms bonded to silicon atoms per molecule of component (e) is less than or equal to 0.01 wt% of the total weight of the composition.
[0021] Component (a)
[0022] The polyorganosiloxane (a) is well known in the art. The alkenyl group is located on the silicon atom at the end of the polyorganosiloxane (a) molecular chain, and the organic groups bonded to the remaining silicon atoms are each independently selected from monovalent organic groups that do not contain aliphatic unsaturated groups.
[0023] The polyorganosiloxane (a) is typically linear. Some exemplary polyorganosiloxanes (a) can be described by the following formula:
[0024] R 1 R 2 2SiO(R 2 2SiO) m SiR 2 2R 1
[0025] In the formula, R 1 Each is an alkenyl group containing 2 to 6 carbon atoms, such as vinyl, allyl, propenyl, butenyl, hexenyl, preferably vinyl, allyl and propenyl, more preferably vinyl;
[0026] R 2Each of the above groups is a monovalent organic group, particularly a monovalent hydrocarbon group, containing 1 to 20 carbon atoms, preferably 1 to 10 carbon atoms, without aliphatic unsaturated groups, and is either substituted or unsubstituted. Examples include alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl; aryl or alkylaryl groups such as phenyl, tolyl, xylyl, mesitylene, ethylphenyl, benzyl, naphthyl; and halogenated or organofunctionalized derivatives of the above groups such as 3,3,3-trifluoropropyl, o-, p- and m-chlorophenyl, aminopropyl, propyl 3-isocyanate, cyanoethyl, preferably methyl and phenyl, more preferably methyl.
[0027] m is a positive number, and m satisfies that the dynamic viscosity of the polyorganosiloxane (a) at 25°C is in the range of 100 to 50,000 mPa·s, for example 200 to 20,000 mPa·s, especially 500 to 10,000 mPa·s.
[0028] In this disclosure, component (a) can be a single polyorganosiloxane containing terminal alkenyl groups, or a mixture of different polyorganosiloxanes containing terminal alkenyl groups, differing, for example, in molecular structure (e.g., the type and number of substituents) or polysiloxane viscosity. For mixtures of polyorganosiloxanes, m represents an average value, and the viscosity range satisfied by m is relative to the viscosity of the mixture.
[0029] Generally, siloxane compositions used as potting materials require low viscosity, and correspondingly, polyorganosiloxanes containing terminal alkenyl groups usually have low viscosity. However, in order to reduce crosslinking density and obtain a low-penetration silicone gel with high elongation at break and excellent viscosity, component (a) of this disclosure preferably also contains a small amount of a high-viscosity polyorganosiloxane containing terminal alkenyl groups.
[0030] In one embodiment, component (a) comprises (a1) a polyorganosiloxane with a dynamic viscosity at 25°C greater than or equal to 100 mPa·s and less than 5,000 mPa·s, containing two alkenyl groups bonded to the terminal silicon atoms of the molecular chain per molecule, and (a2) a polyorganosiloxane with a dynamic viscosity at 25°C greater than or equal to 5,000 mPa·s and less than or equal to 50,000 mPa·s, containing two alkenyl groups bonded to the terminal silicon atoms of the molecular chain per molecule. In the above embodiment, the amount of polyorganosiloxane (a2) is suitably 2 to 20 wt%, for example 5 to 15 wt%, the percentage being based on the total weight of component (a); the molar ratio of the alkenyl groups provided by component (a1) to the alkenyl groups provided by component (a2) is preferably (10 to 50):1.
[0031] In this disclosure, the amount of component (a) is suitably between 20 and 70 wt%, for example, 35 to 55 wt%, the percentage being based on the total weight of the composition.
[0032] Component (b)
[0033] The polyorganosiloxane as component (b) is different from the polyorganosiloxane as component (a) and functions as a crosslinking agent in the composition. The polyorganosiloxane (b) can be linear, branched, or network-like. Linear polyorganosiloxanes (b) are typically composed of polyorganosiloxanes selected from R... 2 3SiO 1 / 2 R 1 R 2 SiO 2 / 2 R 1 R 2 2SiO 1 / 2 and R 2 2SiO 2 / 2 The unit composition, where R 1 R 2 As mentioned above, branched or network-like polyorganosiloxanes (b) also contain, for example, R... 1 SiO 3 / 2 R 2 SiO 3 / 2 The trifunctional unit, and / or SiO 4 / 2 The four functional units, of which R 1 R 2 As mentioned above.
[0034] Some exemplary polyorganosiloxanes (b) include (b1) which are essentially composed of R 1 R 2 2SiO 1 / 2 and SiO 4 / 2 The polyorganosiloxane composed of units, (b2) is basically composed of R 2 3SiO 1 / 2 and R 1 R 2 SiO 2 / 2 The polyorganosiloxane composed of units, (b3) is basically composed of R 1 R 2 2SiO 1 / 2 R 1 R 2 SiO 2 / 2 and R 2 2SiO 2 / 2 Polyorganosiloxanes composed of units, or (b4) basically composed of R 1 R 2 2SiO 1 / 2 R 2 2SiO 2 / 2 and R 2 SiO 3 / 2 Polyorganosiloxane composed of units; wherein R 1 R 2As previously stated, “basic” here means that the polyorganosiloxane (b) contains at least 80 mol%, for example at least 90 mol%, or even at least 95 mol%, of the units listed above.
[0035] In this disclosure, polyorganosiloxane (b1) is particularly preferred, and R 1 R 2 2SiO 1 / 2 unit and SiO 4 / 2 The molar ratio of the units is suitably in the range of (0.4 to 1):1, for example (0.5 to 0.9):1.
[0036] In this disclosure, the amount of component (b) is suitably between 1 and 10 wt%, for example, 2 to 8 wt%, the percentage being based on the total weight of the composition.
[0037] Component (c)
[0038] Component (c) is used as a chain extender in the composition. The dynamic viscosity of component (c) at 25°C is preferably greater than or equal to 30 mPa·s and less than 1,000 mPa·s.
[0039] The polyorganosiloxane(c) is typically linear. Some exemplary polyorganosiloxane(c) can be described by the following formula:
[0040] HR 2 2SiO(R 2 2SiO) n SiR 2 2H
[0041] In the formula, R 2 As mentioned above;
[0042] n is a positive number, and n satisfies that the dynamic viscosity of the polyorganosiloxane (c) at 25°C is greater than or equal to 30 mPa·s and less than 1,000 mPa·s.
[0043] In this disclosure, component (c) can be a single hydrogen-terminated polyorganosiloxane or a mixture of different hydrogen-terminated polyorganosiloxanes, differing, for example, in molecular structure (such as the type and number of substituents) or polysiloxane viscosity. For mixtures of polyorganosiloxanes, n represents an average value, and the viscosity range satisfied by n is relative to the viscosity of the mixture.
[0044] To obtain a low-penetration gel with excellent viscosity, component (c) of this disclosure preferably comprises (c1) a polyorganosiloxane with a dynamic viscosity at 25°C greater than or equal to 30 mPa·s and less than or equal to 200 mPa·s, containing two hydrogen atoms bonded to the terminal silicon atoms of the molecular chain per molecule, and (c2) a polyorganosiloxane with a dynamic viscosity at 25°C greater than 200 mPa·s and less than or equal to 5,000 mPa·s, containing two hydrogen atoms bonded to the terminal silicon atoms of the molecular chain per molecule. In the above embodiments, the molar ratio of SiH groups provided by component (c1) to SiH groups provided by component (c2) is preferably 2:(1 to 10), particularly 1:(1 to 5).
[0045] In this disclosure, component (c) suitably provides 0.6 to 1.0 mol, particularly 0.7 to 0.9 mol, of SiH groups, relative to the 1 mol of silicon-bonded alkenyl groups provided by all components (a) and (b).
[0046] In the compositions disclosed herein, the content of component (c) is suitably 30 to 70 wt%, particularly 40 to 60 wt%.
[0047] Component (d)
[0048] Component (d) can be any type of hydrogen silanization catalyst used in the prior art for addition-curing siloxane compositions, preferably a platinum-based catalyst, such as chloroplatinic acid, chloroplatinate, platinum olefin complexes, or platinum alkenyl siloxane complexes. The amount of the platinum-based catalyst is controlled by considerations of the desired curing rate and economy; generally, only an effective amount as a catalyst for the hydrogen silanization reaction is required. Typically, the weight of platinum metal in the siloxane composition is 0.1–500 ppm, for example, 1–100 ppm.
[0049] Component (e)
[0050] The polyorganosiloxane (e) contains at least three hydrogen atoms bonded to silicon atoms per molecule, and can be linear, cyclic, branched, or network-like. Linear or cyclic polyorganosiloxanes (e) are typically composed of compounds selected from R... 2 3SiO 1 / 2 HR 2 SiO 2 / 2 HR 2 2SiO 1 / 2 and R 2 2SiO 2 / 2 The unit composition, where R 2 As mentioned earlier, branched or network-like polyorganosiloxanes (e) also contain substances such as HSiO. 3 / 2 R 2 SiO 3 / 2 The trifunctional unit, and / or SiO4 / 2 The four functional units, of which R 2 As mentioned above.
[0051] The compositions disclosed herein are preferably free of polyorganosiloxane (e). “Free of” means that the content of polyorganosiloxane (e) in the composition is less than or equal to 0.01 wt%, or even less than or equal to 0.001 wt%.
[0052] Component (f)
[0053] The siloxane compositions disclosed herein may also contain inhibitors (f) to control the usable time and curing rate of the composition. The inhibitors may be various inhibitors conventionally used in the art, such as alkynyl alcohols like 1-ethynyl-1-cyclohexanol and 2-methyl-3-butyn-2-ol, polyvinylsiloxanes like 1,3,5,7-tetravinyltetramethylcyclotetrasiloxane, and alkyl maleates. The amount of the inhibitor can be determined based on the chemical structure of the specific inhibitor selected and the desired curing rate. Generally, these inhibitors are added in amounts of 1 to 50,000 ppm, for example, 10 to 10,000 ppm, relative to the total weight of the composition.
[0054] Other optional ingredients
[0055] The siloxane compositions disclosed herein may also contain fillers as needed. Examples of fillers include, but are not limited to, non-thermally conductive fillers such as calcium carbonate, fumed silica, precipitated silica, silica powder, diatomaceous earth, zirconium silicate, organomontmorillonite, and titanium dioxide, and thermally conductive fillers such as alumina, zinc oxide, magnesium oxide, aluminum hydroxide, aluminum nitride, boron nitride, silicon carbide, aluminum, copper, nickel, gold, silver, graphite, and graphene. It is known in the art that siloxane compositions used for bonding, sealing, potting, and coating protection of electronic components may contain appropriate amounts of fillers; however, siloxane compositions used for potting or optical bonding of displays should not contain fillers due to light transmittance requirements.
[0056] The siloxane compositions disclosed herein may also contain appropriate amounts of other additives, provided that they do not impair the achievement of the objectives of this disclosure. Examples of such additives include, but are not limited to, solvents, diluents and plasticizers, fillers, surface treatment agents, and color pastes. Examples of solvents include decamethylcyclopentasiloxane, hexamethyldisiloxane, octamethyltrisiloxane, heptamethylhexyltrisiloxane, decamethyltetrasiloxane, dodecylpentasiloxane, tetradecylmethylhexasiloxane, and isododecane; examples of diluents and plasticizers include dimethyl silicone oil with a dynamic viscosity of 10–5,000 mPa·s at 25°C and MDT-type silicone oil with a dynamic viscosity of 15–300 mPa·s at 25°C. Preferably, the compositions do not contain any of the above-mentioned additives; "does not contain" means that the amount of additives in the composition is less than 0.1 wt%, or even 0.01 wt%.
[0057] In a preferred embodiment of this disclosure, the siloxane composition comprises:
[0058] (a) 20 to 70 wt% of at least one polyorganosiloxane containing two alkenyl groups bonded to the silicon atoms at the ends of the molecular chain per molecule.
[0059] (b) 1 to 10 wt% of at least one polyorganosiloxane containing at least three alkenyl groups bonded to silicon atoms per molecule.
[0060] (c) 30–70 wt% of at least one polyorganosiloxane containing two hydrogen atoms bonded to the silicon atoms at the ends of the molecular chain per molecule, and
[0061] (d) At least one hydrogenation silanization catalyst.
[0062] The siloxane composition disclosed herein is suitably stored in two or more separate packages, wherein each of the separate packages does not simultaneously contain components (b), (c) and (d), nor does it simultaneously contain components (a), (c) and (d).
[0063] The viscosity of the siloxane composition described in this disclosure is suitably 200 to 10,000 mPa·s at room temperature (23±2) °C, for example 500 to 5,000 mPa·s, particularly 500 to 2,000 mPa·s. The viscosity referred to here is the mixed viscosity of the composition before curing, and when the composition is stored in two or more separate packages, it also refers to the viscosity of the components in each package.
[0064] The second aspect of this disclosure provides a silicone gel obtained by curing a silicone composition of the first aspect of this disclosure.
[0065] The composition described in the first aspect of this disclosure is crosslinked or cured, or the components are mixed as described above in individually packaged form and then crosslinked or cured. The crosslinking or curing is typically carried out at 15–180°C for 10 min–72 h. Low curing temperatures and short curing times are desirable. This disclosure preferably uses curing at 20–80°C for 15–120 min.
[0066] The silicone gel disclosed herein preferably has a penetration value in the range of 20 to 50 according to ASTM D1403 (1 / 4 cone).
[0067] The third aspect of this disclosure provides the use of the siloxane compositions of the first aspect of this disclosure in the bonding, sealing, or coating protection of electronic components.
[0068] The cured product of the siloxane composition disclosed herein is a gel with high elongation at break, excellent resistance to deformation, and excellent conformability, making it suitable for bonding, sealing, or coating protection of electronic components. Such electronic components include, but are not limited to, circuit boards, CPUs, and mobile phones.
[0069] The fourth aspect of this disclosure provides the use of the siloxane compositions of the first aspect of this disclosure in the potting of electronic components or displays.
[0070] The siloxane composition disclosed herein has low viscosity and good flowability, facilitating potting operations. The potting applications include, but are not limited to, pressure sensors, metering sensors, insulated-gate bipolar transistors (IGBTs), and displays, particularly large-size screens such as large educational screens, outdoor displays, large-size touchscreens, and touchscreen displays for automotive, marine, and aerospace applications. These large-size screens are generally 50 inches or larger, and some are even 86 inches or larger.
[0071] By filling the gap between a large-size display screen and a glass cover plate and expelling the air in the gap using the siloxane composition disclosed herein, the display screen can achieve an anti-reflective effect. Furthermore, the cured product of the siloxane composition disclosed herein is a gel with low penetration and excellent viscosity, light transmittance, and negative pressure resistance, making it suitable for potting displays in high-altitude areas.
[0072] The fifth aspect of this disclosure provides the use of the siloxane composition of the first aspect of this disclosure in the optical bonding of displays.
[0073] The cured product of the siloxane composition disclosed herein is a gel with high elongation at break, excellent resistance to deformation and conformability, as well as excellent adhesion and light transmittance, making it suitable for optical bonding of displays, especially large-size screens. Furthermore, the gel of this disclosure has low penetration and excellent resistance to negative pressure, making it suitable for optical bonding in high-altitude areas. Attached Figure Description
[0074] Figure 1 Viscosity test curves of the silicone gels in Examples 1-2 and Comparative Examples 1-2 were plotted. Detailed Implementation
[0075] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.
[0076] Viscosity determination
[0077] The viscosities of components A and B were measured using a Brookfield viscometer with rotor No. 03 at room temperature (23±2)℃ and a rotation speed of 10 rpm.
[0078] Penetration determination
[0079] According to ASTM D1403, the test should be conducted using a 1 / 4 scale cone with a total mass of 9.38 g at room temperature (23±2℃). The diameter of the test specimen should be greater than or equal to 35 mm, and the depth should be greater than or equal to 30 mm. During the test, place the flat-bottomed glass dish containing the cured silicone gel specimen (curing conditions 65℃ for 30 min) on the platform of the needle penetration tester. Move the lifting frame up and down to the appropriate position and tighten it. Then, use the fine-tuning handwheels on both sides to slowly lower the needle connecting rod, using the reflector to observe that the needle tip is just in contact with the specimen surface. Press the zeroing button on the display panel to zero the display. After zeroing for 10 seconds, press the start button. The standard needle will fall into the sample, and the displacement indicator reading should be read. The same specimen should be tested in parallel at least 3 times. The distance between each test point and the edge of the sample dish should not be less than 10 mm. A clean standard needle should be used for each test, or the standard needle should be removed and wiped dry with cotton or cloth soaked in alcohol solvent. The average value of the test results should be taken.
[0080] Determination of Shore A hardness
[0081] According to national standard GB / T531-1999.
[0082] Viscosity measurement
[0083] The texture analyzer was used with a P / 25 test cone for determination. During testing, a flat-bottomed glass dish (35 mm in diameter, 30 mm deep) containing a cured silicone gel sample (cured at 65°C for 30 min) was placed directly below the test cone. The apparatus was turned on, and the test cone moved downwards at a speed of 2 mm / s. After contacting the sample surface, the cone continued to move downwards until it reached 2 mm into the sample, held for 5 seconds to allow for full wetting of the sample. Then, the cone moved upwards at a speed of 2 mm / s until the sample detached from the cone. The force exerted by the cone into and out of the sample, as well as the force-time relationship, could be measured using a sensor. The viscosity of the sample was assessed by the area enclosed by the force-time curve and the time axis below the time axis; a larger area indicated better viscosity.
[0084] High temperature test
[0085] Mix components A and B in a 1:1 ratio using a static mixer. Apply the resulting mixture onto the polarizer of an 80-inch display using a fishbone pattern. Slowly cover the polarizer with a glass cover plate, ensuring no air bubbles are present throughout the process. Then, cure the product at 65°C for 30 minutes. After curing, leave the product at room temperature for 3 days, then place it in a 95°C oven for 200 hours. If no bubbles or cracks appear after 200 hours at 95°C, and no gel peels off from the polarizer or glass cover plate, the product is considered to have passed the high-temperature test.
[0086] negative pressure test
[0087] Mix components A and B in a 1:1 ratio using a static mixer. Apply the resulting mixture onto the polarizer of a 14-inch display using a fishbone pattern. Then, slowly cover it with a glass cover plate, ensuring no air bubbles are present throughout the process. Cur the product at 65°C for 30 minutes. After curing, place the product at room temperature for 3 days, then place it in an environment with negative one atmosphere of pressure for 3 days. If no air bubbles or cracks appear after 3 days of negative one atmosphere of pressure, and no gel peels off from the polarizer or glass cover plate, the product is considered to have passed the negative pressure test.
[0088] The components involved in the following examples and comparative examples
[0089] a1: Dimethylvinylsiloxy-terminated polydimethylsiloxane, with a dynamic viscosity of approximately 1,000 mPa·s at 25°C and a vinyl content of 0.124 mmol / g, supplied by Wacker Chemie.
[0090] a2: Dimethylvinylsiloxy-terminated polydimethylsiloxane, with a dynamic viscosity of approximately 20,000 mPa·s at 25°C and a vinyl content of 0.042 mmol / g, supplied by Wacker Chemie.
[0091] b1: Vinyl MQ resin, with a molar ratio of M units to Q units of 0.7:1 and a vinyl content of 0.78 mmol / g, supplied by Wacker Chemie.
[0092] b2: A trimethylsiloxy-terminated polydimethylsiloxane with multiple vinyl groups in its side chains, having a dynamic viscosity of 340–820 mPa·s at 25°C and a vinyl content of 2.8 mmol / g, provided by Wacker Chemie.
[0093] c1: Dimethylhydrosiloxy-terminated polydimethylsiloxane, with a dynamic viscosity of approximately 65 mPa·s at 25°C and a hydrogen content of 0.53 mmol / g, supplied by Wacker Chemie.
[0094] c2: Dimethylhydrosiloxy-terminated polydimethylsiloxane, with a dynamic viscosity of approximately 1,000 mPa·s at 25°C and a hydrogen content of 0.12 mmol / g, supplied by Wacker Chemie.
[0095] c3: Dimethylhydrosiloxy-terminated polydimethylsiloxane, with a dynamic viscosity of approximately 15 mPa·s at 25°C and a hydrogen content of 1.8 mmol / g, supplied by Wacker Chemie.
[0096] d: Platinum-based catalyst, CATALYST EP, supplied by Wacker Chemie.
[0097] e: Trimethylsiloxy-terminated polydimethylsiloxane with multiple hydrogen atoms in the side chain, dynamic viscosity of approximately 150 mPa·s at 25°C, hydrogen content of 1.8 mmol / g, supplied by Wacker Chemie.
[0098] f: inhibitor INHIBITOR PT 88, supplied by Wacker Chemie.
[0099] g: Methyl MQ resin, MQ 803, supplied by Wacker Chemie.
[0100] Examples 1-2 and Comparative Examples 1-3
[0101] According to the formulation in Table 1, the components of component A and component B are mixed evenly, and then the resulting A and B combination is mixed and cured at 65°C for 30 minutes to obtain silicone gel.
[0102] The penetration test results of the silicone gels in each embodiment and comparative example are shown in Table 2. Among them, the silicone rubber obtained by curing comparative example 3 is not silicone gel, but silicone rubber, and its Shore A hardness was measured.
[0103] Figure 1 Viscosity test curves for the silicone gels of Examples 1-2 and Comparative Examples 1-2 were plotted. Figure 1 It can be seen that the silicone gel of Example 1 has very good adhesion, the silicone gel of Example 2 also has good adhesion, while the silicone gels of Comparative Examples 1-2 have significantly worse adhesion than those of Examples 1-2. The silicone rubber of Comparative Example 3 has no adhesion, so no corresponding tests were performed.
[0104] Table 3 shows that the silicone gels of Examples 1-2 passed the high-temperature and negative-pressure tests. The silicone gel of Comparative Example 1 failed the tests because it developed bubbles or cracks after both the high-temperature and negative-pressure tests. The silicone gel of Comparative Example 2 also failed the tests because it exhibited gel peeling from the polarizer or glass cover after both the high-temperature and negative-pressure tests.
[0105] Table 1
[0106]
[0107] *: No measurement was performed.
[0108] Table 2
[0109] Penetration 32 32 62 31 / Shore A Hardness / / / / 12
[0110] Table 3
[0111] High temperature test pass pass Not approved Not approved negative pressure test pass pass Not approved Not approved
Claims
1. A siloxane composition, characterized in that, Include (a) At least one polyorganosiloxane containing two alkenyl groups bonded to the terminal silicon atoms of the molecular chain per molecule, (b) At least one polyorganosiloxane containing at least three alkenyl groups bonded to silicon atoms per molecule, (c) at least one polyorganosiloxane containing two hydrogen atoms bonded to the silicon atoms at the ends of the molecular chain per molecule, and (d) At least one hydrogenation silylation catalyst; The conditions are that the content of component (c) is greater than or equal to 30 wt% of the total weight of the composition, and the content of at least one polyorganosiloxane containing at least 3 hydrogen atoms bonded to silicon atoms per molecule in component (e) is less than or equal to 0.01 wt% of the total weight of the composition; and Component (c) has a dynamic viscosity at 25°C greater than or equal to 30 mPa·s and less than 1,000 mPa·s. Component (c) comprises (c1) a polyorganosiloxane with a dynamic viscosity at 25°C greater than or equal to 30 mPa·s and less than or equal to 200 mPa·s, containing two hydrogen atoms bonded to the terminal silicon atoms of the molecular chain per molecule, and... (c2) Polyorganosiloxanes with a dynamic viscosity at 25°C greater than 200 mPa·s and less than or equal to 5,000 mPa·s, containing two hydrogen atoms bonded to silicon atoms at the end of the molecular chain per molecule.
2. The siloxane composition according to claim 1, characterized in that, The content of component (c) is greater than or equal to 40 wt% of the total weight of the composition.
3. The siloxane composition according to claim 1, characterized in that, The molar ratio of SiH groups provided by component (c1) to SiH groups provided by component (c2) is 2: (1~10).
4. The siloxane composition according to any one of claims 1 or 2, characterized in that, Compared to the 1 mol of silicon-bonded alkenyl groups provided by all components (a) and (b), component (c) provides 0.6 to 1.0 mol of SiH groups.
5. The siloxane composition according to any one of claims 1 or 2, characterized in that, Component (b) contains at least one polyorganosiloxane selected from the following (b1) By R 1 R 2 2SiO 1 / 2 and SiO 4 / 2 Polyorganosiloxane composed of units, (b2) By R 2 3SiO 1 / 2 and R 1 R 2 SiO 2 / 2 Polyorganosiloxane composed of units, (b3) By R 1 R 2 2SiO 1 / 2 R 1 R 2 SiO 2 / 2 and R 2 2SiO 2 / 2 Polyorganosiloxanes composed of units, and (b4) By R 1 R 2 2SiO 1 / 2 R 2 2SiO 2 / 2 and R 2 SiO 3 / 2 Polyorganosiloxane composed of units; Where R 1 Each is an alkenyl group containing 2 to 6 carbon atoms bonded to silicon atoms, R 2 Each is an independent monovalent hydrocarbon group containing 1 to 20 carbon atoms and without aliphatic unsaturated groups, bonded to silicon atoms.
6. The siloxane composition according to any one of claims 1 or 2, characterized in that, Component (a) contains (a1) Polyorganosiloxanes with a dynamic viscosity at 25°C greater than or equal to 100 mPa·s and less than 5,000 mPa·s, containing two alkenyl groups bonded to the silicon atoms at the ends of the molecular chain per molecule, and (a2) A polyorganosiloxane with a dynamic viscosity at 25°C greater than or equal to 5,000 mPa·s and less than or equal to 50,000 mPa·s, containing two alkenyl groups bonded to the silicon atoms at the end of the molecular chain per molecule.
7. The siloxane composition according to any one of claims 1 or 2, characterized in that, Include (a) 20-70 wt% of at least one polyorganosiloxane containing two alkenyl groups bonded to the terminal silicon atoms of the molecular chain per molecule. (b) 1 to 10 wt% of at least one polyorganosiloxane containing at least three alkenyl groups bonded to silicon atoms per molecule. (c) 30-70 wt% of at least one polyorganosiloxane containing two hydrogen atoms bonded to the silicon atoms at the ends of the molecular chain per molecule, and (d) At least one hydrogenation silylation catalyst; The sum of the wt% of all components is 100%.
8. A silicone gel obtained by curing the siloxane composition according to any one of claims 1 to 7.
9. The silica gel as described in claim 8, characterized in that, The silicone gel has a penetration of 20 to 50, measured using a 1 / 4 cone according to ASTM D1403.
10. Use of the siloxane composition according to any one of claims 1 to 7 as a potting material.
11. The use as described in claim 10, wherein the siloxane composition is used for potting a display.
12. Use of the siloxane composition according to any one of claims 1 to 7 as an optical bonding material.
13. The use as described in claim 12, wherein the siloxane composition is used for optical bonding of a display.
Citation Information
Patent Citations
Silicone skin adhesive gels
EP1737504A1
Low-modulus heat-conducting organopolysiloxane composition as well as preparation method and application thereof
CN111154269A